EVALUATING THE ASSOCIATION BETWEEN VARIOUS INDICATORS OF SCHOOL QUALITY AND EDUCATIONAL OUTCOMES IN SOMALIA WITH SPECIAL REFERENCE TO PUNTLAND STATE - Farah , Abdiqani; Farah, Dahir (African Journal of Education and Practice, 2022)
Purpose: the aim of this quantitative study is to highlight the major obstacles associated with the association between various indicators of school quality and educational outcomes that hinder adequate primary education from taking its foothold in Somalia at large and the federal state of Puntland in particular. Methodology: This study used three retrospective data sources from the previous six school years, as well as raw data on the direct and indirect costs of primary education and their impact upon parents' affordability to send their children to school in the first place, which were collected from 27 primary schools using a cross-sectional approach. The study used descriptive and inferential statistics: compare mean ± SD, t-test and analysis of variance (ANOVA). Results: In each considered scholastic year, on average, 30% of the population reached school-year and 167,439 enrolled, and of that, only a mere 5% qualified for the final year-eight exam. The outcome revealed a massive drop out along the way. Of the two types of primary education mise en scene, Alternative Basic Education (ABE) and Primary & Integrated Qur'anic Schools (PIQS), the parents enrolled their children in the latter on a 1:17 ratio. The enrollment rate of female and male pupils in the last six scholastic years has been 55% and 45%, respectively. The public-school regions examined were found to have been over three-fold higher than the private ones, though this doesn't have an effect on the cost of education per capita. As for the distribution of schools in the nine regions, there is a significant disparity among them, ranging from 32±1 to 128±11. The teacher-student ratio was found to be 36:1±3. The overall average number of teachers over six school-years was found to have been 4,420±458, out of which only 14% (609±104) stood as females, and that is below the 50% sub-Saharan Africa benchmark. Finally, the school cost per child/student in each month has been observed and found to have been 29±7. Consequently, the overall cost for every child per year becomes 234.224 against a background of low family income. Unique contribution to theory, practice and policy: a set of recommendations have been proposed such as: conducting situation analyses on school excellence and educational reforms to be formulated periodically to meet SDG 4 targets; meeting the future needs of education financing; better regulating both public and private schools; closing the gap in teacher-student ratio; the lowest ratio of female teachers in primary education; and for the government to explore in the direction of future education financing in order to better regulate both public and private schools.